Use of evidence in hypertension guidelines: Should we measure in both arms? - Parker, E; Glasziou, P (2009)
For at least 25 years, hypertension guidelines have suggested measuring blood pressure in both arms, but GPs' acceptance of this is low. Current and past versions of major guidelines were identified to review and assess the degree to which they provided justification, evidence, and a description of dual-arm measurement techniques. It is suggested that if guidelines better justified recommendations and cited primary literature to support claims, a greater percentage of practitioners might accept and adhere to such guidance. © British Journal of General Practice.